(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Shobha De is a widely known outspoken journalist and best-sellingIndian writer. Her explosive autobiography, Selective Memory: Stories from MyLife reveals her true self behind the public personality. She candidly writesabout the choices she made, decisions she took, and the influences that shapedher. It is amazing for the openness with which it captures the essence of afascinating woman who has become a legend in her own time. Shobha De does not require an introduction. She is an eminent novelistand columnist of contemporary India, a living legend, who has penned downseveral popular novels; and has here by proved that she possesses anextraordinary degree of creativity and stamina. She belongs to that group ofcontemporary writers of English literature who supports feminism and equalitybetween a man and woman. Feminism, its various aspects and gender equality arethe main themes of the writings of Shobha De. She mainly deals with issuesconcerning the modern society. Shobha De’s maiden novel Socialite Evenings has been criticallyacclaimed and considered a masterpiece in the realm of Feminism. Her secondnovel Starry Nights took the reading world with storm, establishing herreputation as a Popular Culture writer.